Keputusan Bertahan: Inisiatif Sosial Berkelanjutan Usaha Mikro Perhiasan Imitasi Di Desa Sunan Giri, Gresik-Jawa Timur - Uswatun Khasanah; Anita Kristina (Universitas Mercu Buana, 2020)
This study aims to analyze and discuss the survival decisions of imitation jewelry micro business owners. Data collection is done through in-depth interviews with business owners and workers. Then the data are processed and analyzed inductively. The results found that the existence of imitation jewelry business began to change in line with changes in the business environment due to business competition. Another finding is that the business owner decides to stay on his business carried out as a social initiative, namely the owner provides social benefits for the environment and surrounding communities through the creation of jobs based on moral obligations and reinforces the value of togetherness and kinship. The orientation of the decision to survive is not only on economic benefits but on social benefits, through governance based on ethics and existing values. The results of this study can also provide recommendations for further research opportunities, for example the development of research with other issues, namely knowing the transaction costs at each social initiative undertaken by business owners.